Dispossession of Indigenous Peoples’ Living Spaces: Challenges and Prospects for Agrarian Justice in Indonesia - Arrizal, Nizam Zakka; Maharani, Justhine Dian; Adiyatma, Septhian Eka; Baiquni, Muhammad Iqbal (UIR Law Review, 2026)
The dispossession of Indigenous Peoples’ living spaces in Indonesia represents a persistent manifestation of structural inequality in agrarian resource governance. This phenomenon is largely driven by competing interests among Indigenous communities, the state, and corporate actors, resulting in the loss of access to ancestral lands and natural resources, and posing serious threats to cultural integrity, social cohesion, and environmental sustainability. This article examines the key challenges in achieving agrarian justice in Indonesia, particularly the weak legal recognition of customary land rights, regulatory overlap between sectoral laws, and limited substantive participation of Indigenous Peoples in decision-making processes concerning land and resource allocation. Employing a normative legal analysis supported by socio-legal perspectives, this study also explores prospects for strengthening agrarian justice through equitable policy reform. These include the harmonization of agrarian regulations, acceleration of formal recognition of customary territories, strengthening of law enforcement mechanisms against unlawful land appropriation, and meaningful inclusion of Indigenous Peoples in resource governance frameworks. The findings indicate that despite ongoing agrarian reform initiatives, legal and institutional fragmentation continues to undermine effective protection of Indigenous territorial rights. This article contributes to the discourse on agrarian justice by emphasizing the need to reconceptualize land governance through an Indigenous rights-based and sustainability-oriented approach. It argues that achieving agrarian justice in Indonesia requires not only regulatory reform but also a paradigm shift toward participatory and inclusive governance that balances economic development with ecological and cultural preservation.